HPV genotyping in adenocarcinoma of the uterine cervix in Thailand. Issue 3 (10th September 2013) - Siriaunkgul, Sumalee; Utaipat, Utaiwan; Suthipintawong, Cheepsumon; Tungsinmunkong, Kobkul; Triratanachat, Surang; Khunamornpong, Surapan
Abstract: Objective: To determine the distribution of human papillomavirus (HPV) genotypes in cervical adenocarcinoma in Thailand and to evaluate the clinicopathologic characteristics associated with common HPV genotypes. Methods: Formalin‐fixed, paraffin‐embedded tissues from 150 patients with adenocarcinoma were collected from 4 areas of Thailand. Infection with HPV was detected by nested polymerase chain reaction (PCR) with primers MY09/11 and GP5 +/6 +. Genotyping was performed using a linear array assay, followed by type‐specific PCR targeting the E6/E7 regions of HPV‐16, HPV‐18, and HPV‐52 if the linear array test was negative. Results: Human papillomavirus DNA was detected in 145 (97%) adenocarcinomas (132 single infections; 11 multiple infections; 2 tumors with undetermined HPV type). Genotype 18 was most common (66%), followed by HPV‐16 (30%) and HPV‐45 (3%). Infection with only HPV‐16 and/or HPV‐18 accounted for 88% of the HPV‐positive tumors. Patients with HPV‐18 infection had a younger age ( P = 0.009) and higher tumor grade ( P < 0.001) than patients with HPV‐16 infection. Conclusion: The HPV detection rate in cervical adenocarcinomas in Thailand is high. The predominant genotype is HPV‐18, being twice as common as HPV‐16. Genotype variations are associated with patient age and tumor grade. Vaccination against HPV‐16/HPV‐18 might prevent almost 90% of adenocarcinomas.